1997
DOI: 10.1073/pnas.94.25.13515
|View full text |Cite
|
Sign up to set email alerts
|

Topology of allosteric regulation of lactose permease

Abstract: Sugar transport by some permeases in Escherichia coli is allosterically regulated by the phosphorylation state of the intracellular regulatory protein, enzyme IIA glc of the phosphoenolpyruvate:sugar phosphotransferase system. A sensitive radiochemical assay for the interaction of enzyme IIA glc with membrane-associated lactose permease was used to characterize the binding reaction. The N-and C-termini, as well as five hydrophilic loops in the permease, are exposed on the cytoplasmic surface of the membrane an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 29 publications
1
34
3
Order By: Relevance
“…The binding of the sugar induces a structural change, which exposes the substrate binding site to the cytoplasm ("inward"). To explain the observation that EIIA Glc binds to LacY with higher affinity when its substrate is present (597,624,800,825), the "outward"/ "inward" transition is assumed to make the EIIA Glc interaction site more easily accessible (800,823). Evidence supporting this concept comes from studies of a Cys154Gly mutant LacY.…”
Section: Inhibits Transcription Induction Mechanismmentioning
confidence: 82%
See 2 more Smart Citations
“…The binding of the sugar induces a structural change, which exposes the substrate binding site to the cytoplasm ("inward"). To explain the observation that EIIA Glc binds to LacY with higher affinity when its substrate is present (597,624,800,825), the "outward"/ "inward" transition is assumed to make the EIIA Glc interaction site more easily accessible (800,823). Evidence supporting this concept comes from studies of a Cys154Gly mutant LacY.…”
Section: Inhibits Transcription Induction Mechanismmentioning
confidence: 82%
“…For example, EIIA Glc binds strongly to the lactose transporter LacY only in the presence of a ␤-galactoside (597,624,800,825). This mechanism ensures that EIIA Glc , the concentration of which is fairly constant in E. coli and S. enterica serovar Typhimurium cells, will not be wasted on useless binding, i.e., under conditions in which the substrate is not present in the environment.…”
Section: During Inducer Exclusion Unphosphorylated Eiiamentioning
confidence: 99%
See 1 more Smart Citation
“…leucine toxicity ͉ nitrogen-metabolic phosphotransferase system (PTS) ͉ potassium transporter TrkA ͉ protein-protein interaction ͉ signal transduction T he well defined phosphotransferase system (PTS) is composed of two general cytoplasmic proteins, enzyme I (EI) and histidine phosphocarrier protein (HPr), and some sugarspecific components collectively known as enzymes II (1). The carbohydrate PTS, especially for glucose uptake, occupies a central position in bacterial physiology as a result of the identification of multiple regulatory functions superimposed on the transport functions, such as regulation of chemotaxis by EI (2); regulation of glycogen breakdown by HPr (3, 4); regulation of the global repressor Mlc by the membrane-bound glucose transporter EIICB Glc (5-7); and regulation of carbohydrate transport and metabolism (1,8,9), the metabolic flux between fermentation and respiration (10), and adenylyl cyclase activity (11) by EIIA Glc . These regulatory functions of the carbohydrate PTS depend on the phosphorylation state of the involved components, which have been shown to increase in the absence and decrease in the presence of a PTS sugar substrate.…”
mentioning
confidence: 99%
“…In addition to sugar transport, multiple roles are exerted by the PTS and these include chemoreception (3), catabolite repression (4), carbohydrate transport and metabolism (1,5,6), carbon storage (7,8), and the coordination of carbon and nitrogen metabolism (9). More recently, we found that EIIA Glc of the PTS also regulates the flux between respiration and fermentation pathways by sensing the available sugar species via a phosphorylation state-dependent interaction with the fermentation/respiration switch protein FrsA (10).…”
mentioning
confidence: 99%